Legal Protection for Doctors Suffering from Diseases at Work - Handayani, Trini (Interdisciplinary Social Studies, 2022)
Background: PP 88 of 2019 on Occupational Health lists about Occupational Diseases (PAK) is a disease that occurs as a result of work results and or the environment around the workplace. Occupational Diseases must have a direct relationship with exposure experienced by workers, must be scientifically proven and use evidence methods based on evidence based medicine. Aim: As the title indicates, this research aimed to explore more about legal protection for doctors who are infected during work. Method: This is a qualitative or normative research method. Researchers looked at cases of Occupational Diseases in Hospitals and how they were linked to regulations regarding loss reimbursement. Findings: There are cases of Occupational Diseases in Hospitals that until now there has never been compensation as mandated by PP No. 15 of 2019, there needs to be a mechanism in the enforcement of PAK diagnoses and indemnity mechanisms.